Hubungan Tingkat Kecemasan Dengan Tingkat Kepatuhan Perawat Dalam Penggunaan Alat Pelindung Diri Di Ruang Perawatan Pasien Covid - Cintyanisita, Reny; Wardani, Yulia; Suparmi CB, Sr. Lucilla (I Care Jurnal Keperawatan STIKes Panti Rapih, 2022)
Background: Coronavirus disease 2019 (COVID-19) is an infectious disease that caused by SARS-CO-V-2 which has never been found in humans, attacks respiratory systemwith symptoms of fever, cough, shortness of breath. On January 30, 2020, WHO declared Covid-19 as a non-natural disaster caused by the spread of Corona Virus Disease 2019 (Covid-19) and stated the Publik Health Emergency of International on January 30, 2020. One of the issue for health workers is compliance level of the health care worker at hospital so the use of proper personal protective equipment is very important to break the chain of transmission of Covid-19. Purpose: This study aims to determine the relationship between the level of anxiety and the level of compliance of nurses in the use of personal protective equipment in the Covid patient care room at the hospital. Methods: The research method used was quantitative method with descriptive correlatif surveydesign, with a cross sectional approach. The method of collecting data used a questionnaire. With total sampling technique, 58 nurses who served in the Covid patient care room were gathered as the sample in this study. Results: The demographic profile of the respondents were female (84.5%), aged 17-25 years (41.4%), with educational background as D3 Nursing diploma (93.1%), length of work> 3 months (53.4% ), respondents with no anxiety (86.2%), good level of compliance in the use of personal protective equipment (91.4). TheSpearman correlation analysiswas found with p value = 0.359. Conclusion: There is no significant relationship between the level of anxiety and the level of compliance of nurses in the use of personal protective equipment in the private hospital Covid patient care room in Yogyakarta. Keywords: Covid-19, Anxiety, Compliance, PPE